Turkey's strategic autonomy in the Black Sea and the Eastern Mediterranean - Daria Isachenko; Erol Kaymak (Stiftung Wissenschaft und Politik (SWP), 2024)
In the Black Sea, Turkey has been able to engage in resource exploration and joint security arrangements with its neighbours. Ankara's approach to the Black Sea demonstrates that with the right diplomatic efforts and mutual recognition of interests, regional cooperation is possible even in complex geopolitical environments. The contrast in Ankara's positioning in the Black Sea and the Eastern Mediterranean highlights the potential for Turkey to participate in cooperative frameworks in the latter case, provided its concerns and interests are adequately addressed.tion policy is important both for understanding the actions of the invader and for developing action plans for the Ukrainian authorities after the end of the war and the liberation of these territories.
Keywords: 320; Turkey; foreign policy; Recep Tayyip Erdoægan; North Atlantic Treaty Organization (NATO); Russia; European Union (EU); United States (US); Black Sea; Eastern Mediterranean; regional cooperation; Organization of Black Sea Economic Cooperation (BSEC); United Nations Convention on the Law of the Sea (UNCLOS); Blue Homeland doctrine